Causes and Effects of Malnutrition on Academic Performance of Grade 1 Students at San Bartolome Elementary School (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Growing children have their different favorite foods, such as candies, chocolates, hotdogs, ice cream, street foods, chips, fries, soft drinks, junk food, and fast foods. They do not have an idea if it is healthy or not yet. Their parents always want them to eat nutritious foods, but they refuse them. At present, parents often give their children fast food because it is easy to buy; hence, they do not need to think about the next meal. Fast food is also easy to find anywhere. If food preparations are less stressful, then fast food consumption would decrease. There is nothing wrong if a family occasionally goes to a fast-food restaurant as opposed to a family that makes it a regular part of their routine. A child who eats fast food and not junk food frequently are not getting the proper nutrients they need to develop optimally. Junk foods and fast foods lack iron and have excessive amounts of unhealthy fats and added sugar and salt. As a result of not having nutritious food inn their diet, malnutrition will be developed in children. This chapter presents the process that will be used in collecting the data necessary in answering the main and specific problems stated in chapter 1. This includes research designs, respondents of the study, sampling techniques, instrument used in the study, validation of the research instrument, construction of the instrument, and the statistical treatment of data used. The results showed that the highest cause of malnutrition compared with the number of meals a day is a low amount of food, with a weighted mean of 0.8 (80% of 10 respondents). In terms of the effects on physical activities, tiredness is the common effect encountered by the students. During recitation, no self-confidence and inferiority got the highest ranking, followed by poor communication. Based on the summary of the findings, malnutrition affects the academic performance of Grade 1 students in terms of physical (i.e., stunted growth, eye problem, and body weight) and emotional aspects (i.e., loss of appetite, always being mad, sensitive, and moody. In terms of academics, the effects of malnutrition are not being motivated to study, absenteeism, and lack of focus, followed by behavior effects, inattentive, refusal, and getting angry.
Keywords: CEMAP-G1